EFEKTIVITAS PENCEGAHAN MALADMINISTRASI PENDIDIKAN DI OMBUDSMAN KOTA MAKASSAR - Lestari, Sindi; Mappamiring, Mappamiring; Wahid, Nur (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to determine how far the level of effectiveness of preventing maladministration of education by the Ombudsman of Makassar City. This research uses qualitative research with descriptive type. There were seven informants in this study. The research data were collected through observation, interviews, and documentation. Validation of the data is done through triangulation of sources, techniques, and the past time is analyzed through data collection techniques, data reduction, data presentation and drawing conclusions. The results of this study indicate the effectiveness of preventing maladministration in the education sector at the Makassar City Ombudsman in terms of Productivity has been effective from the report, which has been completed, the adaptability has been effective seen from the Ombudsman's relationship with other agencies, job satisfaction has not been maximized, this is evidenced in the provision of salaries, rewards and community satisfaction that has not been fully effective, the search for resources is still not effective, this is evidenced by the education in the field provided that is not appropriate, the intellectual quality and skills that need to be improved as well as the facilities and infrastructure that need to be completed.